Molecular targeting of Glioblastoma – how do you hit a moving target? - Cloughesy, Timothy F. (2011)
Cancer is a molecularly complex, genomically unstable disease. Selection for drug resistance mutations, activation of feedback loops and upregulation of cross-talk pathways provide escape routes by which cancer cells maintain signal flux through critical downstream effectors to promote therapeutic resistance. Targeting signal transduction pathways in cancer may therefore require aiming at a “moving target”. The routes of resistance need to be anticipated to guide the selection of drugs that will lead to durable therapeutic response. In this New Strategies article, we discuss the challenges imposed by the complexity and “adaptive” capacity of cancer and suggest potential new diagnostic strategies in order to more effectively guide targeted cancer therapy. We focus on glioblastoma (GBM), the most common malignant primary brain tumor of adults. GBM is a model for a “pathway-driven”, molecularly heterogeneous cancer for which new genomic insights obtained through The Cancer Genome Atlas are ripe for integration with functional biology and incorporation into new molecular diagnostic assays.